Polydimethylsiloxane matrix and method for its production, fluid guide, heating device

CN122958752APending Publication Date: 2026-10-23ZHUHAI NORUI NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611273759.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-20
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0005]本申请的目的在于提供一种聚二甲基硅氧烷基体及其制备方法、导流体、加热装置,旨在解决如何简单、低成本地制备孔结构可设计且具有优异贯通性的多孔聚二甲基硅氧烷基体,以便很好地用作导流体的技术问题

Benefits of technology

[0020]第四方面,本申请提供一种加热装置,包括本申请第三方面提供的导流体。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122958752A_ABST
    Figure CN122958752A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of substrate preparation processes, in particular to a polydimethylsiloxane substrate and a preparation method thereof, a flow guide and a heating device. The preparation method of the polydimethylsiloxane substrate provided by the application comprises the following steps: providing a non-woven fabric template; filling a mixture containing a dimethylsiloxane prepolymer and a curing agent in the non-woven fabric template, and then performing curing treatment to obtain a composite solid; and removing the non-woven fabric template in the composite solid to obtain the polydimethylsiloxane substrate. The application can utilize the highly designable and controllable characteristics of the pore structure of the non-woven fabric template, and through mutual supplement of the internal structures, efficient copying from a 'template structure' to a 'pore structure' can be realized. The polydimethylsiloxane substrate copied from the non-woven fabric template has the characteristics of three-dimensional interconnection and intercommunication, and the process is simple and easy to realize; therefore, the porous polydimethylsiloxane substrate with excellent through properties can be prepared at low cost and high efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of matrix preparation technology, and particularly relates to a polydimethylsiloxane body and its preparation method, fluid guide, and heating device. Background Technology

[0002] Polydimethylsiloxane (PDMS) possesses excellent biocompatibility, chemical stability, optical transparency, flexibility, and ease of processing, leading to its widespread application in microfluidic chips, flexible electronics, and biomedical engineering. However, traditional bulk PDMS has a dense, non-porous structure and lacks the ability for spontaneous liquid transport and conduction, which limits its application in applications requiring active liquid conduction and storage.

[0003] To impart porous flow properties to polydimethylsiloxane, the following methods are currently used: (1) Particle filtration method: Soluble particles such as salt and sucrose are mixed with polydimethylsiloxane prepolymer, and after solidification, the dissolved particles form pores. The pores formed by this method are random and have poor connectivity, and the porosity and pore structure are not easy to control precisely. (2) Foaming method: Bubbles are generated during the solidification process of polydimethylsiloxane through physical or chemical means. The pore structure of this method has poor uniformity, and most of them are closed or semi-open pores, which is not conducive to long-distance continuous liquid transport, and the process conditions (pressure, temperature) are harsh. (3) 3D printing method: The structure can be customized, but the equipment is expensive, the material compatibility requirements are high, the preparation efficiency is low, and it is difficult to obtain a good porous structure.

[0004] Therefore, the polydimethylsiloxane prepared by the above method has limited improvement on the liquid or gas transport and flow conduction capabilities, and its preparation process as a fluid conduction material needs to be improved. Summary of the Invention

[0005] The purpose of this application is to provide a polydimethylsiloxane body and its preparation method, a fluid conductor, and a heating device, aiming to solve the technical problem of how to prepare porous polydimethylsiloxane bodies with designable pore structures and excellent permeability in a simple and low-cost manner so that they can be well used as fluid conductors.

[0006] To achieve the above-mentioned objectives, the technical solution adopted in this application is as follows: In a first aspect, this application provides a method for preparing a polydimethylsiloxane, comprising: Non-woven fabric templates are available; A mixture containing dimethylsiloxane prepolymer and curing agent is filled into the nonwoven template and then cured to obtain a composite solid. The nonwoven template in the composite solid is removed to obtain polydimethylsiloxane.

[0007] The method for preparing polydimethylsiloxane in this application uses a nonwoven fabric template as a removable template. Polydimethylsiloxane raw material is filled into the nonwoven fabric template and cured. Then, the nonwoven fabric template is removed to obtain a bulk-connected polydimethylsiloxane. Because the pore structure of the nonwoven fabric template is highly designable and controllable, efficient replication from the "template structure" to the "pore structure" can be achieved through the mutual topology of its internal structures. The polydimethylsiloxane channels replicated from the template have three-dimensional interconnectedness. Moreover, this process is simple and easy to implement, and can prepare porous polydimethylsiloxane with excellent interconnectivity at low cost and high efficiency. Therefore, the polydimethylsiloxane prepared in this application can provide an ideal path for efficient and low-resistance transport of liquids or gases, and can be well used as a fluid conductor.

[0008] In some possible implementations, the nonwoven template has a three-dimensional network structure formed by multiple fibers, and the average diameter of the fibers is 1μm to 25μm.

[0009] In some possible implementations, the basis weight of the nonwoven template is 25 g / m². 2 ~1100g / m 2 ; And / or, the thickness of the nonwoven fabric template is 0.15mm~10mm; And / or, the porosity of the nonwoven fabric template is 60%~98%; And / or, the average pore size of the nonwoven template is 5μm~400μm.

[0010] In some possible implementations, the nonwoven template includes a needle-punched nonwoven fabric, wherein the needle-punching density of the needle-punched nonwoven fabric is 50 needles / cm² to 500 needles / cm², and the needle-punching depth is 2mm to 20mm. Alternatively, the nonwoven template may include a spunlace nonwoven fabric, and the spunlace pressure of the spunlace nonwoven fabric is 20 bar to 150 bar.

[0011] In some possible implementations, the material of the nonwoven template includes at least one of polylactic acid, polycaprolactone, polyurethane, and polyvinyl alcohol.

[0012] In some possible implementations, the removal of the nonwoven template from the composite solid includes: The composite solid is placed in a solvent that can dissolve the nonwoven template but not the polydimethylsiloxane for dissolution treatment, and then taken out and dried.

[0013] In some possible implementations, the material of the nonwoven template is selected from polylactic acid, and the solvent includes at least one of chloroform, dichloromethane, and tetrahydrofuran; or the material of the nonwoven template is selected from polycaprolactone, and the solvent includes at least one of dichloromethane and ethyl acetate; or the material of the nonwoven template is selected from polyurethane or polyvinyl alcohol, and the solvent includes at least one of N,N-dimethylformamide and dimethyl sulfoxide. And / or, the dissolution treatment time is 2h~48h; And / or, the dissolution process is carried out under ultrasonic and / or stirring conditions.

[0014] In some possible implementations, the curing temperature is 40°C to 100°C; and / or the curing time is 0.5h to 4h.

[0015] In some possible implementations, the mass ratio of the dimethylsiloxane prepolymer to the curing agent is (5~15):1; And / or, the mixture is filled into the nonwoven template by vacuum injection.

[0016] In a second aspect, this application provides a polydimethylsiloxane body prepared by the preparation method provided in the first aspect of this application; the polydimethylsiloxane body has a porosity of 1% to 50% and an average pore size of 1 μm to 30 μm.

[0017] The polydimethylsiloxane provided in this application is prepared by the unique preparation method described above. Because it uses a nonwoven fabric template, the porous polydimethylsiloxane has excellent permeability. Therefore, the polydimethylsiloxane of this application can provide an ideal path for efficient and low-resistance transport of liquids or gases and can be well used as a fluid conductor.

[0018] Thirdly, this application provides a fluid conductor, including the polydimethylsiloxane body provided in the second aspect of this application.

[0019] The fluid conductor of this application includes the polydimethylsiloxane body of this application. The porous polydimethylsiloxane body has excellent permeability. Therefore, the fluid conductor of this application has excellent liquid or gas transport and conduction capabilities.

[0020] Fourthly, this application provides a heating device including the fluid guide provided in the third aspect of this application.

[0021] The heating device provided in this application includes the fluid conductor of this application, which can efficiently and with low resistance transport liquids or gases and has excellent flow conduction capability. Therefore, the heating device has a good heating effect when it is working.

[0022] The above description is only an overview of the technical solution of this application. In order to better understand the technical means of this application and to implement it in accordance with the contents of the specification, and to make the above and other objects, features and advantages of this application more obvious and understandable, the following are specific embodiments of this application. Attached Figure Description

[0023] To more clearly illustrate the technical solutions in the embodiments of this application, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0024] Figure 1 This is a SEM image of the polydimethylsiloxane fluid provided in Example 1 of this application.

[0025] Figure 2 This is a SEM image of the polydimethylsiloxane fluid provided in Example 2 of this application.

[0026] Figure 3 This is a SEM image of the polydimethylsiloxane fluid provided in Example 3 of this application.

[0027] Figure 4 This is a SEM image of the polydimethylsiloxane fluid provided in Example 4 of this application. Detailed Implementation

[0028] To make the technical problems, technical solutions, and beneficial effects of this application clearer, the following detailed description is provided in conjunction with embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.

[0029] In this application, the term "and / or" describes the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. A and B can be singular or plural. The character " / " generally indicates that the preceding and following related objects have an "or" relationship.

[0030] In this application, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refer to any combination of these items, including any combination of single or multiple items. For example, "at least one of a, b or c", or "at least one of a, b and c", can both mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.

[0031] It should be understood that in the various embodiments of this application, the order of the above processes does not imply the order of execution. Some or all steps may be executed in parallel or sequentially. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of this application.

[0032] The terminology used in the embodiments of this application is for the purpose of describing particular embodiments only and is not intended to be limiting of this application. The singular forms “a,” “the,” and “the” used in the embodiments of this application and the appended claims are also intended to include the plural forms unless the context clearly indicates otherwise.

[0033] The weights of the relevant components mentioned in the embodiments of this application can refer not only to the specific content of each component, but also to the proportional relationship between the weights of the components. Therefore, any scaling up or down of the content of the relevant components according to the embodiments of this application is within the scope disclosed in the embodiments of this application. Specifically, the mass described in the embodiments of this application can be a well-known unit of mass in the chemical industry, such as µg, mg, g, or kg.

[0034] The terms "first" and "second" are used only to describe purpose, to distinguish purposes such as substances from one another, and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature.

[0035] The term "liquid matrix" refers to a raw material that, upon heating, can generate a two-phase mixture in which "a gas serves as a continuous medium, and tiny solid particles or liquid droplets are uniformly suspended in the gas." It is a basic component used in heating devices, whether in liquid, solid, or paste form. Liquid matrix components can consist of various flavorings and aromatic substances. Heating and vaporizing the liquid matrix forms the aforementioned two-phase mixture for the user to inhale.

[0036] The term "heating device" refers to a device that can heat a substance, such as a liquid matrix, to form a two-phase mixture, such as a liquid heating device or an electronic heating device. Heating devices typically use built-in heating elements (e.g., heating cores) to precisely heat a specially formulated liquid matrix to a specific temperature, causing some substances in the liquid matrix to evaporate and generate a two-phase mixture for user use. The liquid in a liquid heating device includes not only cases where the substance to be heated is liquid, but also cases where solid substances (including pastes) liquefy under certain conditions.

[0037] The term "non-woven fabric," scientifically known as nonwoven cloth, is distinct from traditional woven and knitted fabrics: non-woven fabrics do not use spinning or weaving processes, but instead directly bond fibers together in a sheet-like material through processes such as bonding, thermal rolling, or hydroentangling, without warp or weft yarns.

[0038] The term "fluid conductor," also known as a liquid-conducting matrix or porous liquid-conducting component, refers to a liquid supply system that relies on capillary micropores. It serves as a liquid transport bridge between the heating wire / heating film and the liquid storage tank.

[0039] Polylactic acid (PLA) is a biodegradable thermoplastic polyester with excellent spinnability. Through needle punching or hydroentangling processes, PLA fibers can be processed into nonwoven fabrics with a three-dimensional network structure, high porosity, and strong inter-fiber entanglement. PLA is soluble in common organic solvents such as chloroform, dichloromethane, and tetrahydrofuran, while PDMS is very stable in these solvents after curing. This property makes PLA a potential candidate for use as a "sacrificial template."

[0040] To address the problems of uncontrollable pore structure, poor connectivity, and complex processes in existing PDMS porous material preparation methods, this application develops a method for preparing a porous PDMS matrix that is simple in process, low in cost, has a highly designable pore structure, and excellent connectivity. This allows the prepared PDMS matrix product to be used as a fluid conductor in heating devices. The technical solution is described in detail below.

[0041] In a first aspect, embodiments of this application provide a method for preparing a polydimethylsiloxane body. Specifically, the preparation method of this application includes: S01: Provide non-woven fabric templates; S02: A mixture containing dimethylsiloxane prepolymer and curing agent is filled into a nonwoven template and then cured to obtain a composite solid. S03: Remove the nonwoven template from the composite solid to obtain polydimethylsiloxane.

[0042] The method for preparing polydimethylsiloxane in this application embodiment uses a nonwoven fabric template as a removable template. The polydimethylsiloxane raw material is filled into the nonwoven fabric template and cured. Then, the nonwoven fabric template is removed to obtain a polydimethylsiloxane with a through-hole structure. Because the pore structure of the nonwoven fabric template is highly designable and controllable, and its internal structure is mutually topologically integrated, efficient replication from the "template structure" to the "pore structure" can be achieved. The polydimethylsiloxane channels replicated from the template have the characteristic of three-dimensional interconnection. Moreover, this process is simple and easy to implement, and can prepare porous polydimethylsiloxane with excellent interconnectivity at low cost and high efficiency.

[0043] The polydimethylsiloxane body prepared in this application not only retains the excellent flexibility, biocompatibility, and chemical stability of polydimethylsiloxane itself, but also acquires lightweight, highly elastic, and liquid-absorbing properties. Furthermore, the hardness and mechanical properties of the porous material can be controlled by adjusting the curing ratio of the polydimethylsiloxane. Therefore, the polydimethylsiloxane body prepared in this way has broad application prospects. For example, the polydimethylsiloxane body prepared by this method can be used as a porous fluid conductor, and can be directly used in the fabrication of flexible microfluidic channel core layers, substrates for stretchable sweat-wicking electronic devices, inner cores of intelligent negative pressure dressings that promote wound healing, and flexible functional materials for directional liquid transport, etc.

[0044] Step S01: Provide a template, i.e., a nonwoven fabric template. The nonwoven fabric template can be made by spreading short fibers or filaments into a fiber web, and then fixing and shaping it in various ways, such as the reinforcement / shaping methods from fiber to nonwoven fabric, such as needle punching, hydroentangling, spunbonding, etc.

[0045] In some possible implementations, the nonwoven template has a three-dimensional network structure formed by multiple fibers, with the average diameter of the fibers ranging from 1 μm to 25 μm. Exemplarily, the average fiber diameter can be any value or a range between any two values, such as 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, 21 μm, 22 μm, 23 μm, 24 μm, 25 μm, etc. By selecting the average fiber diameter in the nonwoven template, the pore size distribution of the final polydimethylsiloxane can be well controlled.

[0046] The fibers used can be short fibers or continuous long fibers, without particular limitation. Long fibers can be continuous fibers, typically reaching several kilometers in length during production. Short fibers can be natural fibers or artificially synthesized chemical long fibers cut to a certain length to mimic natural fibers. Generally, the fiber length in the nonwoven fabric template of this application embodiment can be greater than or equal to 15mm. For example, the fiber length can be 15mm to 150mm, and can be selected according to actual needs.

[0047] In some possible implementations, the nonwoven template has a basis weight of 25 g / m². 2 ~1100g / m 2 For example, the basis weight of the nonwoven fabric template can be 25 g / m². 2 30g / m 2 40g / m 2 50g / m 2 60g / m 2 80g / m 2 100g / m 2 150g / m 2 200g / m 2 250g / m 2 300g / m 2 350g / m 2 400g / m 2 450g / m 2 500g / m 2 550g / m 2 600g / m 2 650g / m 2 700g / m 2 750g / m 2 800g / m 2 850g / m 2 900g / m 2 950g / m 2 1000g / m 2 1100g / m 2 And so on, the range formed by any value or any two values.

[0048] In some possible implementations, the thickness of the nonwoven template is 0.15mm to 10mm; for example, the thickness of the nonwoven template can be any value or a range formed between any two values, such as 0.15mm, 0.2mm, 0.5mm, 1mm, 2mm, 3mm, 4mm, 5mm, 6mm, 7mm, 8mm, 9mm, 10mm, etc.

[0049] The basis weight and thickness of the nonwoven fabric template can determine the bulk density of the nonwoven fabric, which in turn can effectively control the pore size distribution of the final polydimethylsiloxane.

[0050] In some possible implementations, the porosity of the nonwoven template is 60% to 98%; for example, the porosity of the nonwoven template can be any value or a range between any two values, such as 60%, 62%, 65%, 68%, 70%, 72%, 75%, 78%, 80%, 85%, 88%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 98%. In some possible implementations, the average pore size of the nonwoven template is 5 μm to 400 μm; exemplaryly, the average pore size of the nonwoven template can be any value or a range between any two values, such as 5 μm, 10 μm, 20 μm, 40 μm, 50 μm, 80 μm, 100 μm, 120 μm, 150 μm, 180 μm, 200 μm, 250 μm, 280 μm, 300 μm, 320 μm, 350 μm, 380 μm, 400 μm. By controlling the porosity and average pore size of the nonwoven template, suitable mechanical properties can be achieved, facilitating the filling of mixtures containing prepolymers.

[0051] In some embodiments, the average fiber diameter in the nonwoven template is 1μm~25μm, and the basis weight of the nonwoven template is 25g / m². 2 ~1100g / m 2 The thickness of the nonwoven fabric template is 0.15mm to 10mm. Furthermore, the porosity of the nonwoven fabric template is 60% to 98%, and the average pore size of the nonwoven fabric template is 5μm to 400μm.

[0052] By preparing a nonwoven template with a certain thickness, density, and three-dimensional network structure, and controlling parameters such as fiber fineness, needle punching density / hydraulic pressure, and nonwoven fabric surface density, the porosity and fiber arrangement of the template can be pre-designed. In other words, by adjusting various parameters of the nonwoven template, polydimethylsiloxanes with different porosities, pore sizes, and thicknesses can be prepared.

[0053] In some possible implementations, the nonwoven template includes a needle-punched nonwoven fabric with a needle-punching density of 50 needles / cm² to 500 needles / cm² and a needle-punching depth of 2mm to 20mm. Exemplarily, the needle-punching density of the nonwoven fabric can be 50 needles / cm², 60 needles / cm², 70 needles / cm², 80 needles / cm², 90 needles / cm², 100 needles / cm², 120 needles / cm², or 140 needles / cm². / cm², 160 stitches / cm², 180 stitches / cm², 200 stitches / cm², 250 stitches / cm², 280 stitches / cm², 300 stitches / cm², 320 stitches / cm², 360 stitches / cm², 380 stitches / cm², 400 stitches / cm², 420 stitches / cm², 450 stitches / cm², 480 stitches / cm², 500 stitches / cm², etc., any value or a range between any two values.

[0054] In some possible implementations, the nonwoven template includes a spunlace nonwoven fabric, and the spunlace pressure of the spunlace nonwoven fabric is 20 bar to 150 bar. Exemplarily, the spunlace pressure of the spunlace nonwoven fabric can be any value or a range between any two values, such as 20 bar, 30 bar, 40 bar, 50 bar, 60 bar, 70 bar, 80 bar, 90 bar, 100 bar, 110 bar, 120 bar, 130 bar, 140 bar, 150 bar, etc.

[0055] In some possible implementations, the material of the nonwoven template includes at least one of polylactic acid, polycaprolactone, polyurethane, and polyvinyl alcohol.

[0056] Polylactic acid (PLA) is a biodegradable thermoplastic polyester with excellent spinnability. Through processes such as needle punching or hydroentangling, PLA fibers can be made into nonwoven fabrics with a three-dimensional network structure, high porosity, and strong inter-fiber entanglement. PLA is soluble in common organic solvents such as chloroform, dichloromethane, and tetrahydrofuran, while PDMS is very stable in these solvents after curing. This characteristic makes PLA a potential "sacrificial template." Furthermore, the fiber diameter, orientation, arrangement density, and thickness of PLA nonwoven fabrics are highly adjustable, allowing the formation of a three-dimensional network of intertwined fibers and continuously interconnected pores. PDMS channels replicated using this network as a template are also three-dimensionally interconnected, providing an ideal path for efficient and low-resistance transport of liquids and gases, exhibiting excellent flow conductivity. In addition, PLA-based nonwoven templates offer the advantage of relatively controllable template pore size, and PLA's solubility in common solvents minimizes solvent residue. Polycaprolactone, polyurethane, and polyvinyl alcohol can also be used as template materials. Solvents that can dissolve these template materials but not polydimethylsiloxane can be selected for template removal treatment to prepare polydimethylsiloxane bodies.

[0057] Step S02: Fill the nonwoven template with a mixture containing prepolymer.

[0058] The polydimethylsiloxane prepolymer and its curing agent are mixed in a certain proportion and then degassed to obtain a mixture.

[0059] In some possible implementations, the mass ratio of dimethylsiloxane prepolymer to curing agent is (5~15):1. Exemplarily, the ratio of dimethylsiloxane prepolymer to curing agent can be any one or a range of any two values, such as 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, etc. For example, Dow Corning Sylgard 184 (prepolymer and curing agent kit) can be used.

[0060] In some possible implementations, the molecular weight of the dimethylsiloxane prepolymer in the mixture of dimethylsiloxane prepolymer and curing agent can be selected from 200 to 30,000, for example, from 1,500 to 5,000; the curing agent can be selected according to the specific reaction type, for example, it can be hydrogen-containing silicone oil, platinum catalyst, tetraethyl orthosilicate and dibutyltin, etc.

[0061] In some possible implementations, the mixture is filled into the nonwoven template using a vacuum infusion method. The PDMS prepolymer and its curing agent are mixed in a specific ratio, degassed, and then vacuum infused to fully impregnate and fill the entire three-dimensional porous network of the nonwoven template, followed by curing. PDMS curing can be achieved using a photocuring agent, ultraviolet irradiation, or both for cross-linking and curing.

[0062] In some possible implementations, the curing temperature is 40℃ to 100℃; exemplaryly, the curing temperature can be any value or a range between any two values, such as 40℃, 50℃, 60℃, 70℃, 80℃, 90℃, 100℃, etc. In some possible implementations, the curing time is 0.5h to 4h; exemplaryly, the curing time can be any value or a range between any two values, such as 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, etc. These curing conditions allow PDMS to fully crosslink and polymerize, forming a composite solid in which the fiber network of the spun fabric template is embedded in the PDMS matrix.

[0063] Step 03, Non-woven fabric template removal process.

[0064] In some possible implementations, the removal of the nonwoven template from the composite solid includes: placing the composite solid in a solvent that can dissolve the nonwoven template but not the polydimethylsiloxane, performing a dissolution treatment, and then removing and drying it.

[0065] The solvent used in the removal process is an organic solvent that can dissolve the nonwoven template but not polydimethylsiloxane. Through the diffusion and dissolution of solvent molecules, the fibers of the nonwoven template are dissolved and removed.

[0066] In some possible implementations, the nonwoven template material is selected from polylactic acid, and the corresponding solvent includes at least one of chloroform, dichloromethane, and tetrahydrofuran; or the nonwoven template material is selected from polycaprolactone, and the corresponding solvent includes at least one of dichloromethane and ethyl acetate; or the nonwoven template material is selected from polyurethane or polyvinyl alcohol, and the corresponding solvent includes at least one of N,N-dimethylformamide and dimethyl sulfoxide. The above combinations of solvents and nonwoven template materials can dissolve the corresponding nonwoven template but not the cured polydimethylsiloxane, thus providing a good removal effect on the nonwoven template without damaging the polydimethylsiloxane.

[0067] In some possible implementations, the dissolution treatment time is 2 hours to 48 hours; for example, the dissolution treatment time can be any value or a range between any two values, such as 2 hours, 3 hours, 5 hours, 10 hours, 15 hours, 18 hours, 20 hours, 25 hours, 28 hours, 30 hours, 35 hours, 40 hours, 45 hours, 48 ​​hours, etc. Within these timeframes, the nonwoven fabric template can be fully dissolved.

[0068] In some possible implementations, the dissolution process is carried out under ultrasonic and / or stirring conditions. The composite solid is dissolved in a solvent capable of dissolving the nonwoven template but not the polydimethylsiloxane, and ultrasonication or stirring may be used to accelerate the dissolution process.

[0069] In some possible implementations, ultrasound can be performed for 5 to 10 minutes every 0.5 to 4 hours.

[0070] After dissolution, the sample is removed, rinsed again with the same solvent, and dried to obtain a porous polydimethylsiloxane body with three-dimensional interconnected channels, which can be used as a fluid conductor. The drying method can be either room temperature (25℃~30℃) evaporation drying or critical point drying to maintain the pore structure.

[0071] In some possible implementations, embodiments of this application provide a method for preparing a porous polydimethylsiloxane (PDMS) matrix based on a polylactic acid (PLA) nonwoven fabric template, comprising the following steps: (1) Template Preparation: PLA fibers are used to prepare PLA nonwoven templates with a certain thickness, density, and three-dimensional network structure through a needle-punching reinforcement process. By controlling parameters such as fiber fineness, needle-punching density / hydraulic pressure, and nonwoven fabric surface density, the porosity and fiber arrangement of the template can be pre-designed. For example, the diameter of PLA fibers is 1μm~25μm, and short fibers or continuous long fibers can be used. The basis weight of the PLA nonwoven template is 25g / m³. 2 ~1100g / m 2 The thickness of the PLA nonwoven template is 0.15mm~10mm, the needle-punching density of the needle-punched nonwoven fabric is 50 needles / cm²~500 needles / cm², and the hydroentangling pressure of the spunlace nonwoven fabric is 20bar~150bar.

[0072] (2) PDMS filling and curing: After mixing the PDMS prepolymer and its curing agent in a certain proportion and degassing, the mixture is vacuum-infused to fully impregnate and fill the entire three-dimensional porous network of the PLA nonwoven fabric template. Subsequently, heat curing is performed to fully crosslink and polymerize the PDMS, forming a PLA / PDMS composite solid with the PLA fiber network embedded in the PDMS matrix. For example, the mass ratio of PDMS prepolymer to curing agent can be 5:1 to 15:1. The curing temperature can be 40℃ to 100℃, and the curing time can be 0.5 hours to 4 hours.

[0073] (3) Template Removal: The composite solid is immersed in an organic solvent (such as chloroform, dichloromethane, tetrahydrofuran, etc.) that can dissolve PLA but not the cured PDMS. Through the diffusion and dissolution of solvent molecules, the PLA fiber template is fully dissolved and removed. Subsequently, the sample is taken out, rinsed with fresh solvent, and dried to obtain a porous PDMS matrix with three-dimensional interconnected channels. For example, the solvent dissolution time can be 2 hours to 48 hours, during which ultrasound or stirring can be used to accelerate dissolution. The drying method is room temperature (25℃~30℃) evaporation drying or critical point drying to maintain the pore structure.

[0074] In this embodiment, biodegradable polylactic acid (PLA) nonwoven fabric is used as a three-dimensional template to prepare polydimethylsiloxane body with an interconnected porous structure through the above preparation method. It has good liquid or gas transport and flow conduction capabilities, and therefore can be used as a PDMS fluid conductor.

[0075] Secondly, embodiments of this application provide a polydimethylsiloxane body. Specifically, the polydimethylsiloxane body of this application embodiment is prepared by the preparation method provided in the first aspect of this application embodiment; and the porosity of the polydimethylsiloxane body is 1%~50%, and the size of the polydimethylsiloxane body is 1μm~30μm.

[0076] The polydimethylsiloxane body of this application embodiment is prepared using a nonwoven fabric template. Moreover, the porosity of the polydimethylsiloxane body is 1% to 50%, and the average pore size of the polydimethylsiloxane body is 1 μm to 30 μm. It has a porous structure with excellent bulk permeability. Therefore, it can provide an ideal path for efficient and low-resistance transport of liquids or gases and can be well used as a fluid conductor.

[0077] In some possible implementations, the porosity of the polydimethylsiloxane is 1% to 50%; exemplaryly, the porosity of the polydimethylsiloxane can be any value or a range between any two values, such as 1%, 2%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 42%, 45%, 48%, 50%. In some possible implementations, the polydimethylsiloxane has a pore size of 1 μm to 26 μm; exemplaryly, the average pore size of the polydimethylsiloxane can be any value or a range between any two values, such as 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, 22 μm, 25 μm, 26 μm, 28 μm, 30 μm.

[0078] The porosity and average pore size of polydimethylsiloxane (PDMS) can be obtained by controlling relevant parameters of the nonwoven template. Furthermore, PDMS exhibits excellent pore tortuosity and three-dimensional connectivity. Ultimately, the pore size distribution, porosity, pore tortuosity, and three-dimensional connectivity of PDMS can be precisely "pre-coded" during the nonwoven template preparation stage, achieving replication from the "template structure" to the "pore structure."

[0079] Thirdly, embodiments of this application provide a fluid guide. Specifically, the fluid guide of this application includes the polydimethylsiloxane provided in the second aspect of this application.

[0080] The fluid guiding material in this embodiment includes the polydimethylsiloxane body of this embodiment. The porous polydimethylsiloxane body has excellent permeability. Therefore, the fluid guiding material in this embodiment has excellent liquid or gas transport and guiding capabilities.

[0081] Fourthly, embodiments of this application provide a heating device. Specifically, the heating device provided by this application includes the fluid guide provided in the third aspect of embodiments of this application.

[0082] The fluid guiding the device in this embodiment can efficiently and with low resistance transport liquids or gases, and has excellent flow guiding ability. Therefore, the heating device has a good heating effect when it is working.

[0083] In some possible implementations, the heating device contains a liquid matrix. Specifically, the heating device of this application embodiment includes a heating core and a liquid matrix contained within the heating core, with the heating core nested within the fluid guide of this application embodiment.

[0084] The following description is based on specific embodiments.

[0085] Example 1 The preparation of a polydimethylsiloxane fluid includes the following steps: Step 1: Preparation of nonwoven fabric template.

[0086] PLA short fibers with a diameter of 15±2μm and a length of 38mm are carded into a web and then reinforced by needle punching at a density of 300 needles / cm². 2 The needle-punching depth is 8mm, resulting in a PLA needle-punched nonwoven fabric template with a basis weight of 200±10g / m² and a thickness of 2.0±0.2mm.

[0087] Step 2: Filling and curing the prepolymer mixture.

[0088] Dow Corning Sylgard 184 (prepolymer and curing agent kit): Mix the prepolymer and curing agent at a mass ratio of 15:1, mechanically stir for 5 minutes, and then vacuum degas for 30 minutes until no bubbles remain. Place the PLA nonwoven fabric template in the mold, evacuate to -0.095 MPa, and maintain for 15 minutes; then inject the PDMS prepolymer mixture, restore to normal pressure, and continue vacuum infusion for 10 minutes. Ensure complete impregnation. Heat in a 100°C oven for 4 hours to obtain a PLA / PDMS composite solid, where PDMS fully fills the fiber gaps.

[0089] Step 3: Remove the non-woven fabric template.

[0090] The composite solid was immersed in 500 mL of dichloromethane and allowed to stand at room temperature for 24 hours, during which time it was sonicated for 10 minutes every 2 hours. The sample was then removed and rinsed three times with fresh dichloromethane for 15 minutes each time. The sample was then dried in a desiccator to obtain a porous polydimethylsiloxane conductive fluid.

[0091] Example 2 The preparation of a polydimethylsiloxane fluid includes the following steps: Step 1: Preparation of nonwoven fabric template.

[0092] PLA short fibers with a diameter of 5±1μm and a length of 38mm were carded into a web and then reinforced by needle punching. The needle punching density was 300 needles / cm² and the needle punching depth was 8mm, resulting in a PLA needle-punched nonwoven fabric template with a basis weight of 50±5g / m² and a thickness of 0.15±0.02mm.

[0093] Step 2: Filling and curing the prepolymer mixture.

[0094] Dow Corning Sylgard 184 prepolymer and curing agent were mixed at a mass ratio of 5:1, mechanically stirred for 5 min, and then vacuum degassed for 30 min. A PLA nonwoven fabric template was placed in a mold, and a vacuum was drawn to -0.095 MPa and maintained for 15 min. The PDMS mixture was then injected, and after restoring to normal pressure, vacuum infusion continued for 10 min. The mixture was then heated in a 40℃ oven for 0.5 h to obtain the PLA / PDMS composite solid.

[0095] Step 3: Remove the non-woven fabric template.

[0096] The composite solid was immersed in 500 mL of chloroform and allowed to stand at room temperature for 48 hours, during which time it was sonicated for 10 minutes every 4 hours. After removal, it was rinsed three times with fresh chloroform for 15 minutes each time. The sample was then dried in a desiccator to obtain porous PDMS conductive fluid.

[0097] Example 3 The preparation of a polydimethylsiloxane fluid includes the following steps: Step 1: Preparation of nonwoven fabric template.

[0098] PLA short fibers with a diameter of 15±2μm and a length of 31mm were carded into a web and then reinforced by needle punching. The needle punching density was 300 needles / cm² and the needle punching depth was 8mm, resulting in a PLA needle-punched nonwoven fabric template with a basis weight of 50±5g / m² and a thickness of 2.0±0.2mm.

[0099] Step 2: Filling and curing the prepolymer mixture.

[0100] Dow Corning Sylgard 184 prepolymer and curing agent were mixed at a mass ratio of 10:1, mechanically stirred for 5 min, and then vacuum degassed for 30 min. A PLA nonwoven fabric template was placed in a mold, and a vacuum was drawn to -0.095 MPa and maintained for 15 min. The PDMS mixture was then injected, and after restoring to normal pressure, vacuum infusion continued for 10 min. The mixture was then heated in an oven at 80℃ for 2 h to obtain the PLA / PDMS composite solid.

[0101] Step 3: Remove the non-woven fabric template.

[0102] The composite solid was immersed in 500 mL of tetrahydrofuran and allowed to stand at room temperature for 2 h, during which time it was sonicated for 10 min every 0.5 h (40 kHz, 100 W). After removal, it was rinsed three times with fresh tetrahydrofuran for 15 min each time. The sample was then dried in a desiccator to obtain porous PDMS conductive fluid.

[0103] Example 4 The preparation of a polydimethylsiloxane fluid includes the following steps: Step 1: Preparation of nonwoven fabric template.

[0104] PLA short fibers with a diameter of 25±3μm and a length of 38mm were carded into a web and then reinforced by needle punching. The needle punching density was 300 needles / cm² and the needle punching depth was 8mm, resulting in a PLA needle-punched nonwoven fabric template with a basis weight of 600±5g / m² and a thickness of 8.0±0.5mm.

[0105] Step 2: Filling and curing the prepolymer mixture.

[0106] Dow Corning Sylgard 184 prepolymer and curing agent were mixed at a mass ratio of 10:1, mechanically stirred for 5 min, and then vacuum degassed for 30 min. A PLA nonwoven fabric template was placed in a mold, and a vacuum was drawn to -0.095 MPa and maintained for 15 min. The PDMS mixture was then injected, and after restoring to normal pressure, vacuum infusion continued for 10 min. The mixture was then heated in an oven at 80℃ for 2 h to obtain the PLA / PDMS composite solid.

[0107] Step 3: Remove the non-woven fabric template.

[0108] The composite solid was immersed in 500 mL of chloroform and allowed to stand at room temperature for 24 hours, during which time it was sonicated for 10 minutes every 2 hours. After removal, it was rinsed three times with fresh chloroform for 15 minutes each time. The sample was then dried in a desiccator to obtain porous PDMS conductive fluid.

[0109] [Performance Testing] See Table 1 for relevant tests.

[0110] Table 1

[0111] In Table 1, the average pore size and porosity were tested according to GB / T 21650.1-2026 "Determination of Pore Size Distribution and Porosity of Solid Materials by Mercury Porosimetry and Gas Adsorption Methods - Part 1: Mercury Porosimetry". The basis weight of nonwoven fabrics was tested according to GB / T 24218.1-2009. The thickness of nonwoven fabrics was tested according to GB / T 24218.2-2009. The fiber diameter of nonwoven fabrics was tested according to GB / T20732-2006 "Optical Analyzer for Fiber Diameter", and the fiber length was tested according to GB / T 6098-2018 "Test Method for Cotton Fiber Length - Roller Analyzer Method".

[0112] Scanning electron microscope (SEM) images of the polydimethylsiloxane conductive fluids prepared in Examples 1 to 4 are shown below. Figures 1 to 4 .

[0113] The experimental results above show that, in this embodiment, the pore size distribution and porosity of the PDMS fluid can be controlled by adjusting the fiber size, arrangement density, and nonwoven fabric thickness of the PLA nonwoven template. Furthermore, the PDMS fluid channels are interconnected and have excellent connectivity, providing an ideal path for efficient and low-resistance transport of liquids and gases, exhibiting excellent conductivity. It can serve as a good fluid conductor in heating devices. In addition, the preparation process described in this embodiment is simple, low-cost, and environmentally friendly: the main processes (nonwoven fabric forming, impregnation and curing, and dissolution) are mature and easily scalable industrial technologies with low equipment requirements. Moreover, PLA is biodegradable and the solvent is recyclable, resulting in a low environmental burden. The removal of the nonwoven template is gentle, requiring no strong acids or alkalis or high-temperature burning, reducing the risk of damaging the PDMS's properties.

[0114] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and not to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. These modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application, and they should all be covered within the scope of the claims and specification of this application. In particular, as long as there is no structural conflict, the various technical features mentioned in the embodiments can be combined in any way. This application is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.

Claims

1. A method for preparing a polydimethylsiloxane, characterized in that, include: Non-woven fabric templates are available; A mixture containing dimethylsiloxane prepolymer and curing agent is filled into the nonwoven template and then cured to obtain a composite solid. The nonwoven template in the composite solid is removed to obtain polydimethylsiloxane.

2. The preparation method according to claim 1, characterized in that, The nonwoven template has a three-dimensional network structure formed by multiple fibers, and the average diameter of the fibers is 1μm~25μm.

3. The preparation method according to claim 1, characterized in that, The nonwoven fabric template has a basis weight of 25 g / m². 2 ~1100g / m 2 ; And / or, the thickness of the nonwoven fabric template is 0.15mm~10mm; And / or, the porosity of the nonwoven fabric template is 60%~98%; And / or, the average pore size of the nonwoven template is 5μm~400μm.

4. The preparation method according to claim 1, characterized in that, The nonwoven template includes needle-punched nonwoven fabric, and the needle-punching density of the needle-punched nonwoven fabric is 50 needles / cm² to 500 needles / cm², and the needle-punching depth is 2mm to 20mm. Alternatively, the nonwoven template may include a spunlace nonwoven fabric, and the spunlace pressure of the spunlace nonwoven fabric is 20 bar to 150 bar.

5. The preparation method according to any one of claims 1-4, characterized in that, The material of the nonwoven template includes at least one of polylactic acid, polycaprolactone, polyurethane, and polyvinyl alcohol.

6. The preparation method according to any one of claims 1-4, characterized in that, The process of removing the nonwoven template from the composite solid includes: The composite solid is placed in a solvent that can dissolve the nonwoven template but not the polydimethylsiloxane for dissolution treatment, and then taken out and dried.

7. The preparation method according to claim 6, characterized in that, The material of the nonwoven template is selected from polylactic acid, and the solvent includes at least one of chloroform, dichloromethane, and tetrahydrofuran; or the material of the nonwoven template is selected from polycaprolactone, and the solvent includes at least one of dichloromethane and ethyl acetate; or the material of the nonwoven template is selected from polyurethane or polyvinyl alcohol, and the solvent includes at least one of N,N-dimethylformamide and dimethyl sulfoxide. And / or, the dissolution treatment time is 2h~48h; And / or, the dissolution process is carried out under ultrasonic and / or stirring conditions.

8. The preparation method according to any one of claims 1-4, characterized in that, The curing temperature is 40℃~100℃; and / or the curing time is 0.5h~4h.

9. The preparation method according to any one of claims 1-4, characterized in that, The mass ratio of the dimethylsiloxane prepolymer to the curing agent in the mixture is (5~15):1; And / or, the mixture is filled into the nonwoven template by vacuum injection.

10. A polydimethylsiloxane, characterized in that, It is prepared by the preparation method according to any one of claims 1-9; the porosity of the polydimethylsiloxane is 1%~50%, and the average pore size of the polydimethylsiloxane is 1μm~30μm.

11. A fluid conductor, characterized in that, Includes the polydimethylsiloxane as described in claim 10.

12. A heating device, characterized in that, Includes the fluid conductor as described in claim 11.